Individual variation of in-air female ‘pup contact’ calls in Weddell seals, Leptonychotes weddellii - K Collins; T Rogers; J Terhune; P McGreevy; K Wheatley; R Harcourt (2005)
Vocal recognition may function as a critical factor in maintaining the phocid mother-pup bond during lactation. For vocal recognition to function, the caller must produce individually distinct calls that are recognised by their intended recipient. Mother-pup vocal recognition has been studied extensively in colonial otariids and appears to be characteristic of this family. Although less numerous, empirical studies of phocid species have revealed a range of recognition abilities. This study investigated whether Weddell seal (Leptonychotes weddellii) females produce individually distinct 'pup contact' calls that function during natural pair reunions. Fifteen calls from each of nine females recorded in the Vestfold Hills, Antarctica were analysed. One temporal, nine fundamental frequency and five spectral characteristics were measured. Results of the cross-validated Discriminant Function Analysis revealed that mothers produce individually distinct calls with 56% of calls assigned to the correct individual. The probability of achieving this level of discrimination on novel data by chance alone is highly improbable. Analysis of eight mother-pup reunions recorded near McMurdo Sound, Antarctica further demonstrated that these 'pup contact' calls function during natural pair reunions. Behavioural analysis also revealed that pups were chiefly responsible for establishing and maintaining close contact throughout the reunion process. Our study therefore demonstrates that Weddell seal females produce calls with sufficient stereotypy to allow pups to identify them during pair reunions, providing evidence of a functioning mother-pup vocal recognition system.